Inhibition performance of three naphthyridine derivatives for mild steel corrosion in 1M HCl: Computation and experimental analyses - Verma, Chandrabhan; Sorour, Ahmad A.; Ebenso, Eno.E.; Quraishi, M.A. (Elsevier B.V., 2018)
The influence of three naphthyridines (NTDs) on acidic dissolution of mild steel was evaluated using experimental methods. Protection abilities of the NTDs molecules are increases with their concentrations. Maximum inhibition efficiency of 98.69% was observed for NTD-3 molecule at its 4.11 × 10−5 mol/L−1 concentration. The inhibition efficiencies of NTDs molecules followed the order: NTD-1 (96.1%) < NTD-2 (97.4%) < NTD-3 (98.7%). Polarization study showed that NTDs acted as mixed type inhibitors and they preferably block the active sites accountable for the corrosion. EIS study suggested that the NTDs inhibit corrosion because of their adsorption at electrolyte/metal interfaces and their adsorption followed Langmuir adsorption isotherm. AFM analysis was adopted to support the adsorption inhibitive behavior of NTDs.
Keywords: Mild steel Naphthyridines Aggressive solution Electrochemical studies AFM Acid inhibitors